THE EFFECTIVENESS OF DIGITAL MEDIA IN ELEMENTARY SCHOOL DURING THE COVID-19 PANDEMIC - Fahmi Surya Adikara; Dwi Cahaya Nurani; Muhammad Arif Rahman (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2022)
The Covid-19 pandemic has brought big changes to the world of education in Indonesia. Learning that should be done in person or face-to-face turns into online learning. This raises problems for the readiness of schools, teachers, and students in carrying out learning. This study aims to obtain information about the effectiveness of digital media in online learning during the Covid-19 pandemic, whether digital media has been effective and its use is optimal in learning. This research is a qualitative descriptive study using an online survey method. The results obtained were that online learning using digital media at SDN 1 Gambasan Temanggung did not increase student scores because only about 20% of student scores had increased, 50% of students also complained about the lack of facilities and infrastructure that support learning. Teachers also have not been able to use digital media in accordance with the characteristics of learning, this is evidenced by 45% of students answered disagree. Students also do not have higher motivation when using digital media, it is proven that only 5% agree. Based on the research results, it can be concluded that digital media is less effective when the supporting facilities and infrastructure are minimal.